Journey to the river sea - Ibbotson, Eva.; Hawkes, Kevin (New York : Puffin, 2003)
Sent with her governess to live with the dreadful Carter family in exotic Brazil in 1910, Maia endures many hardships before fulfilling her dream of exploring the Amazon River.
"Originally published in Great Britain by Macmillan Children's Books, London, 2001"--T.p. verso.
School Library Journal starred
Wilson's Children
Wilson's Junior High School
6.3
5-8.
Keywords: Adventure and adventurers -- Fiction; Governesses -- Fiction; Historical fiction; Orphans -- Fiction; Adventure fiction; Governesses -- Fiction; Historical fiction; Orphans -- Fiction; Amazon River Region -- Fiction; Brazil -- History -- 1889-1930 -- Fiction; Amazon River Region -- Fiction; Brazil -- History -- Fiction